2008
DOI: 10.1007/s00248-008-9444-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Short-Term Antibiotic Effects on Respiration and Bacterial Growth Compromises the Validity of the Selective Respiratory Inhibition Technique to Distinguish Fungi and Bacteria

Abstract: The selective inhibition (SI) technique has been widely used to resolve fungal and bacterial biomass. By studying bacterial growth (leucine/thymidine incorporation) and respiration simultaneously, this study demonstrates that the inhibitors the SI technique is based on do not efficiently or specifically resolve fungal and bacterial contributions to respiration. At concentrations that completely inhibited bacterial growth, the bactericide streptomycin had no influence on the SI technique's respiration measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 45 publications
6
50
1
Order By: Relevance
“…Using this technique, increases in the fungal biomass/bacterial biomass ratio of 4.5-fold between pH 7 and 3 (12) and of twoto sixfold between pH 6 and 3 (17) have been reported. However, the partitioning of potential respiration by using antibiotics to estimate fungal and bacterial biomasses has repeatedly been challenged (56,64). Still, it is noteworthy that this biomass technique, which inherently relies on active microorganisms, has high responsiveness to pH effects.…”
Section: Vol 75 2009 Contrasting Ph Effects On Fungal and Bacterialmentioning
confidence: 99%
“…Using this technique, increases in the fungal biomass/bacterial biomass ratio of 4.5-fold between pH 7 and 3 (12) and of twoto sixfold between pH 6 and 3 (17) have been reported. However, the partitioning of potential respiration by using antibiotics to estimate fungal and bacterial biomasses has repeatedly been challenged (56,64). Still, it is noteworthy that this biomass technique, which inherently relies on active microorganisms, has high responsiveness to pH effects.…”
Section: Vol 75 2009 Contrasting Ph Effects On Fungal and Bacterialmentioning
confidence: 99%
“…Other recent studies provide evidence in support of the concept of functional redundancy. Rousk et al (2009) concluded that functional redundancy in carbon mineralization was exhibited in fungal and bacterial communities in upland soils along a pH gradient, as respiration was relatively unchanged despite significant differences in microbial growth. An overlap in biogeochemical function and ecology of bacteria and fungi was also proposed by Strickland and Rousk (2010) to account for a lack of correlation between changing trends in cycling of key elements and shifts in fungal:bacterial dominance.…”
Section: Functional Redundancy In Carbon Mineralization Across Peatlamentioning
confidence: 99%
“…The authors concluded that the various biomass methods agreed and that fungi usually dominated the biomass of soil microbes. However, the widely used method of selective inhibition of respiration (Bååth and Anderson 2003) has recently been shown to overestimate fungal respiration, since respiration of many bacteria is also limited by supposedly fungal-specific inhibitors (Rousk et al 2009). …”
Section: Amino Acid Cycling In Terrestrial Soilsmentioning
confidence: 99%